2022
DOI: 10.3389/fpubh.2022.1015952
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastasis risk and prognosis assessment models for kidney cancer based on machine learning

Abstract: BackgroundBone metastasis is a common adverse event in kidney cancer, often resulting in poor survival. However, tools for predicting KCBM and assessing survival after KCBM have not performed well.MethodsThe study uses machine learning to build models for assessing kidney cancer bone metastasis risk, prognosis, and performance evaluation. We selected 71,414 kidney cancer patients from SEER database between 2010 and 2016. Additionally, 963 patients with kidney cancer from an independent medical center were chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Composite diagnostic and prognostic models have been applied clinically for diagnosing various bone metastases. For example, a machine learning-based renal cancer bone metastasis risk model constructed based on the SEER database can accurately predict the risk and prognosis of renal cancer bone metastasis, which improves decision-making in the care of patients with renal cancer 20 . A previous study showed that a diagnostic risk model based on colon cancer pathology classi cation, lymph node metastasis, and visceral metastasis could identify patients with colon cancer at high risk of bone metastasis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Composite diagnostic and prognostic models have been applied clinically for diagnosing various bone metastases. For example, a machine learning-based renal cancer bone metastasis risk model constructed based on the SEER database can accurately predict the risk and prognosis of renal cancer bone metastasis, which improves decision-making in the care of patients with renal cancer 20 . A previous study showed that a diagnostic risk model based on colon cancer pathology classi cation, lymph node metastasis, and visceral metastasis could identify patients with colon cancer at high risk of bone metastasis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al developed an ML model (KCBM) utilizing the SEER database of 71,414 kidney cancer patients to evaluate bone metastasis and long-term survival in this population. The KCBM achieved an AUC of 0.8269 (95% CI: 0.8083-0.8425) [64]. Another study conducted by Feng et al also utilized the SEER database and analyzed data from 39,016 patients to develop six ML models for predicting lymphatic metastasis in kidney cancer.…”
Section: Ai In Predicting Kidney Cancer Outcomesmentioning
confidence: 99%
“…Among them, the ML method has been widely used in cancer prognosis research, such as laryngeal cancer, lung cancer, breast cancer, kidney cancer, malignant pleural mesothelioma, etc. [7,[10][11][12][13] . Indeed, it effectively offers accurate prognoses based on the cancer sample data [14] .…”
Section: Introductionmentioning
confidence: 99%